I've been trying to solve it for quite some time but I still don't get it why it is true.

The original equation is: \begin{equation*} 1-\frac{\sin{^2}\theta}{1-\cos\theta}=-\cos\theta. \end{equation*} My work so far: \begin{equation*} \frac{1-\cos\theta}{1-\cos\theta}-\frac{\sin{^2}\theta}{1-\cos\theta} =\frac{1-\cos\theta-\sin{^2}\theta}{1-\cos\theta} =\frac{(1-\sin{^2}\theta)-\cos\theta}{1-\cos\theta} \\ =\frac{\cos{^2}\theta-\cos\theta}{1-\cos\theta} =\frac{\cos\theta(\cos\theta-1)}{1-\cos\theta}. \end{equation*} I saw on some sites that this is equal to $-\cos\theta$ but I don't see why.

  • 1
    $\begingroup$ You've got $\cos(\theta)-1$ in the numerator which is $-1\cdot(1-\cos(\theta))$. Now cancel and you're done. $\endgroup$ – Michael Burr May 14 '15 at 15:54
  • $\begingroup$ $\cos x-1=-(1-cos x)$ $\endgroup$ – E.H.E May 14 '15 at 15:54

$\textbf{hint}$ $$ \cos\theta -1 = -(1-\cos\theta) $$

  • $\begingroup$ Got it. Thanks! $\endgroup$ – Dormin May 14 '15 at 17:20

You're very close. From where you left off





  • $\begingroup$ Some equals signs would be nice. $\endgroup$ – N. F. Taussig May 15 '15 at 20:30

Shorter: $$1-\frac{\sin{^2}\theta}{1-\cos\theta}=-\cos\theta\iff 1+\cos\theta=\frac{\sin{^2}\theta}{1-\cos\theta}\iff 1-\cos^2\theta=\sin^2\theta.$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.